1612 Sporadic AOPTD is a genetic disorder: evidence from the temporal discrimination threshold. Issue 3 (9th February 2012) - Kimmich, O; Bradley, D; Whelan, R; Mulrooney, N; Reilly, R B; Hutchinson, S; O'Riordan, S; Hutchinson, M
Abstract : Introduction: Adult-onset primary torsion dystonia (AOPTD) is an autosomal dominant disorder with markedly reduced penetrance; sporadic AOPTD patients are much more prevalent than familial. The temporal discrimination threshold (TDT) is the shortest time interval at which two stimuli are detected to be asynchronous and has been shown to be abnormal in AOPTD. Aim/Hypothesis: The aim was to determine the frequency of abnormal TDTs in sporadic AOPTD patients and their first degree relatives. We hypothesised that abnormal TDT s in first degree relatives would be compatible with an autosomal dominant endophenotype. Methods: TDTs were examined in 61 control subjects (39 under 50 years, 22 over 50 years), 32 sporadic AOPTD patients (30 cervical dystonia, 1 spasmodic dysphonia, one Meige's Syndrome) and 73 unaffected first degree relatives (36 siblings, 36 offspring and one parent) using visual and tactile stimuli. Z-scores were calculated for all subjects; a Z-score >2.5 was considered abnormal. Results: The mean TDT in controls under 50 was 24.54 ms and 31.11 ms in controls over 50. Abnormal TDTs (Z-score >2.5) were found in 1 of 61 (2%) control subjects, 27 of 32 (84%) AOPTD patients and 32 of 73 (44%) unaffected relatives [siblings (20/36; 56%), offspring (11/36; 31%) and one parent]. When two or more relatives were tested in any one family, 22 of 24 families had at least one first degree relative with an abnormal TDT. Conclusion: The frequency of abnormal TDTs in first degree relatives of patients with sporadic AOPTD is compatible with an autosomal dominant disorder and supports the hypothesis that apparently sporadic AOPTD is genetic in origin.